The Effect of Using Think Pair Share (TPS) Cooperative Learning Models Towards Mastery of Student`s Concept and Learning Activities - Ana Septiana Fatmawati; Arwin Achmad; Pramudiyanti Pramudiyanti (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The average students` score of  Growth and Development in living organisms concepts was   lower compared to score of the average  school. This study aimed to determine the effect of  Think Pair Share (TPS) cooperative learning models  to increase the mastery of the  students learning activities and  concept mastery  of Growth and Development in living organisms. This study used pretest-postest not equivalent designed  applied on sample which was selected using cluster random sampling technique. The data of this study was obtained from the test (pretest and posttest) and the observation sheet (students learning activities). Data was analyzed  using  t-test through  SPSS17 program.Based on the data analyzed,  the of N-gain score of experimental class on student`s concept mastery  was higher  than the control class. Students learning activities  used TPS model tend to  increase  from the first lesson to the third lesson with the average  of 17.34 %.The  study showed that the application of cooperative learning model type TPS affecting student`s concept  mastery and learning activities on the concept of Growth and Development in living organisms. Keywords: TPS  model learning, concept mastery , students` learning activities